The Influence of Local Cultural Values and Nostalgic Expectations on Consumer Purchasing Decisions of Lontong Orari Banjarmasin - Adista Anjar Diany; Rika Yuliyanti (PT. Anagata Sembagi Education, 2025)
Indonesia is a culturally diverse country where each region possesses unique cultural and culinary traits that shape the identity of its local communities. In Banjarmasin, one of the most popular traditional foods that has gained significant recognition and public favor is Lontong Orari. This research aims to investigate how local cultural values and nostalgic expectations influence consumer purchasing decisions toward Lontong Orari. The study employs a quantitative associative method with an explanatory approach. The population consists of consumers who have previously purchased and consumed Lontong Orari, using a sample of 100 respondents selected through purposive sampling. The data were analyzed using the Structural Equation Model (SEM) through the SmartPLS 3.0 software. Findings reveal that both local cultural values and nostalgic expectations significantly influence consumer behavior in making purchasing decisions. Local culture plays a crucial role in shaping consumer identity and preferences, while nostalgia triggers emotional connections that drive consumers to choose traditional foods like Lontong Orari. This study highlights the importance of integrating cultural and emotional elements into marketing strategies for traditional culinary products, especially in preserving regional identity and promoting local economic development through culinary heritage..